Jesus' Resurrection and Collective Hallucinations - Jake H. O'Connell (Tyndale Bulletin, 2009)
This study is divided into two parts. Part I examines modern accounts of collective religious visions. Five factors make it very likely that such visions are collective hallucinations. Part II examines whether the same is true of Jesus’ resurrection appearances. The evidence indicates that if the resurrection appearances were collective hallucinations, hallucinations of glorious appearances of Jesus would have occurred alongside hallucinations of non-glorious appearances. Since the Gospels relate only non-glorious appearances of Jesus, hallucinations can only be maintained as an explanation if the original tradition of glorious/non-glorious appearances was changed to a tradition of purely non-glorious appearances. However, there are strong reasons to believe that the early church would have preserved, not eliminated, traditions of glorious appearances, had such existed. The lack of glorious appearances in the Gospels is therefore an indicator that the appearances were originally non-glorious and thus not hallucinations. Thus, collective hallucinations provide an inadequate explanation for the resurrection appearances.